PERLINDUNGAN HUKUM PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA UNTUK MEWUJUDKAN REFORMASI BIROKRASI - Nurmalita Ayuningtyas Harahap (Justitia et Pax, 2016)
ABSTRACT In the Law No. 5 of 2014 concerning the State Civil Apparatus has emerged a new terminology named Te Government Contract Workers. Te presence of the Government Contract Workers followed by a reason but as part of the Bureaucratic Reform to improve the professionalism of the state apparatus, one of which is done by structuring the management system in terms of procurement and the appointment of the State Civil Apparatus.But, the law protection provided by the Government for the Government Contract Workers is perceived not enough. Terefore, the form of law protection that should be given are rights received by the Government Contract Workers related with welafare, appointment of the Government Contract Workers to be the Government Permanent Workers, Issue Te Government Regulations about Te Government Contract Workers Management. Keywords:Law Protection,TeGovernment Contract Workers, Bureaucratic Reform INTISARI Dalam Undang-Undang No. 5 Tahun 2014 tentang Aparatur Sipil Negara telah muncul peristilahan baru, yaitu Pegawai Pemerintah dengan Perjanjian Kerja (PPPK). Adanya PPPK bukan tanpa alasan namun sebagai bagian dari reformasi birokrasi untuk meningkatkan profesionalisme aparatur negara yang salah satunya dilakukan dengan penataan sistem manajemen dalam hal pengadaan dan pengangkatan Aparatur Sipil Negara. Tetapi, perlindungan hukum yang diberikan Pemerintah untuk PPPK saat ini masih dirasa belum cukup. Oleh karena itu bentuk perlindungan hukum yang seharusnya diberikan yaitu mengenai hak yang diterima PPPK yang terkait dengan kesejahteraan, pengangkatan PPPK menjadi PNS, menerbitkan Peraturan Pemerintah tentang manajemen PPPK. Kata Kunci: Perlindungan Hukum, Pegawai Pemerintah dengan Perjanjian Kerja, Reformasi Birokrasi.